Anti-dementia medication use in Aotearoa New Zealand: An exploratory study using health data from the Integrated Data Infrastructure (IDI). (June 2023) - Chan, Amy Hai Yan; Hikaka, Jo anna; To, Edith; Cullum, Sarah; Ma'u, Etuini; Ryan, Brigid; Rivera-Rodriguez, Claudia; Cheung, Gary
Objective: Anti-dementia medications such as acetylcholinesterase inhibitors are an important part of the management pathway for dementia. However, there are limited data in New Zealand that have examined the rates and patterns of use of funded anti-dementia medication and how use differs with ethnicity, age and sex. Methods: This was a retrospective population-based descriptive study. Using the Integrated Data Infrastructure, we identified individuals of all ages coded for a diagnosis of dementia and estimated the proportion dispensed funded anti-dementia medication – donepezil tablets and rivastigmine patches – between 1 July 2016 and 30 June 2020. Rates of medication use in five main ethnic groups (Māori, Pacific peoples, Asian, European, and Middle Eastern, Latin American and African) in the <65, 65–79 and 80 and over (80+) age groups were compared and also between males and females in all sub-groups. Log-binomial models were used to calculate relative risks to determine any differences in anti-dementia medication use in the five ethnic groups and the three age groups and between males and females in each of the four study years. Results: Overall, one-third of the dementia population received a funded anti-dementia medication in the total population (all ages) between 2016 and 2020. Donepezil tablets were dispensed in 31.6–34.0% and rivastigmine patches in 1.4–2.1% across the four study years. Compared to people of European ethnicity, Māori, Pacific peoples, and Middle Eastern, Latin American and African groups were less likely to be dispensed an anti-dementia medication (Māori: relative risk = 0.79–0.81, p < 0.0001; Pacific peoples: relative risk = 0.72–0.74, p < 0.0001; Middle Eastern, Latin American and African: relative risk = 0.73–0.78, p < 0.05). Compared to the age 80+ group, the 65–79 age group was more likely (relative risk = 1.50–1.54, p < 0.0001), while the age <65 group was less likely (relative risk = 0.67–0.71, p < 0.0001) to be dispensed an anti-dementia medication. There were no statistically significant differences in anti-dementia medication use between males and females. Conclusion: This study provides important information about funded anti-dementia medication use in New Zealand and how this differs by ethnicity, age and sex. Despite higher dementia prevalence in Māori and Pacific peoples, these groups were less likely to receive funded anti-dementia medication.